Assessing impacts of COVID-19 pandemic on animal source food retailers and consumers in Vietnam and Cambodia - Sinh Dang-Xuan; Nga Nguyen Thi Duong; Ty, C.; Hung Pham-Van; Unger, Fred; Hung Nguyen-Viet (International Livestock Research Institute, 2022)
Objectives: The study aimed to assess the impact of COVID-19 pandemic on business activities and food safety practices of animal source food (ASF) retailers and consumers during the first wave of COVID-19 pandemic from February to April 2020 in Vietnam and Cambodia. Materials and methods: This study was conducted as a cross-sectional study using a face-to-face interview, after the first wave of COVID-19 pandemic occurring in Vietnam and Cambodia. A total of 608 participants (n=300 ASF retailers and 308 consumers), represented both rural and peri-urban/urban areas, was included. Results: Eighty-six percent (258/300) ASF retailers reported that their income deceased with average of 48.2%, 11% without changing, and 2.7% increased (by 32.5%) during the social distancing period. While 54.3% (163/300) reported their decreased income at 37.7%, 36.0% (108/300) without changing, and 9.3% increase (by 26.6%) after the first wave of COVID-19. There was no significant difference in income decrease between rural and peri-urban/urban sellers either during social (p=0.76, t.test) or after COVID-19 (p=0.53, t.test). During the social distancing, 27% retailers revealed it was more difficult to source ASF to sell but facilitated increasing food safety practice compliance. Seventy-four (228/308) consumers had income decreased from 20-35% mainly due to reduced jobs, no significant difference was observed between rural and urban consumers. Almost 80% of consumers agreed that they had better practices in looking for a good hygiene practice shop to buy ASF, washing hands and kitchen equipment as due to COVID-19 pandemic. Conclusion: These findings suggest that COVID-19 pandemic affected negatively business activities and incomes of ASF retailers and consumers. However, food safety behaviours were improved. Relevant recommendations need to be formulated to support ASF retailing business and improve food safety practices of both retailers and consumers because of COVID-19.